2022
DOI: 10.3389/fnins.2022.854219
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial Magnetic Stimulation for Improving Dysphagia After Stroke: A Meta-Analysis of Randomized Controlled Trials

Abstract: BackgroundRehabilitation of post-stroke dysphagia is an urgent clinical problem, and repetitive transcranial magnetic stimulation (rTMS) has been widely used in the study of post-stroke function. However, there is no reliable evidence-based medicine to support the effect of rTMS on post-stroke dysphagia. This review aims to evaluate the effectiveness and safety of rTMS on post-stroke dysphagia.MethodsEnglish-language literature published before December 20, 2021, were searched in six electronic databases. Iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 46 publications
0
26
0
Order By: Relevance
“…rTMS is also shown to be effective in rehabilitation of dysphagia after stroke in recent published systematic reviews [54,55]. The mean difference was −1.03 with p value <0.0001 in Penetration Aspiration Scale after completion of TMS [55].…”
Section: Other Therapeutic Usesmentioning
confidence: 94%
See 1 more Smart Citation
“…rTMS is also shown to be effective in rehabilitation of dysphagia after stroke in recent published systematic reviews [54,55]. The mean difference was −1.03 with p value <0.0001 in Penetration Aspiration Scale after completion of TMS [55].…”
Section: Other Therapeutic Usesmentioning
confidence: 94%
“…Neuropathic pain is one of the big topics in pain management, and TMS is shown to be an effective tool in managing those patients [52,53]. rTMS is also shown to be effective in rehabilitation of dysphagia after stroke in recent published systematic reviews [54,55]. The mean difference was −1.03 with p value <0.0001 in Penetration Aspiration Scale after completion of TMS [55].…”
Section: Other Therapeutic Usesmentioning
confidence: 98%
“…In terms of treatment acceptability, both rTMS and tDCS are well tolerated and no serious adverse effects have been reported [103,104 ▪▪ ].…”
Section: Treatment Strategiesmentioning
confidence: 97%
“…Some meta-analyses found more significant effects of rTMS when using high-frequency stimulation, which increases cortical activity [102,105]. Conversely, other authors found more significant effects of inhibitory, low-frequency rTMS [103]. Conflicting findings are partly because of the low number of studies, assessing the therapeutic effects of low-frequency rTMS [106].…”
Section: Treatment Strategiesmentioning
confidence: 99%
“…The study by Zhu and Gu ( 2022 ) showed that rTMS increased swallowing function compared with the sham stimulation group [SMD = 1.08 (0.37, 1.80), I 2 = 81.2%, p < 0.001]. Xie et al ( 2022a , b ) reported two articles about the influence of rTMS for dysphasia after stroke, and the effect value showed [SMD = −0.76 (−1.07, −0.46), ( p < 0.001)] and [SMD = −0.87 (−1.22, −0.52), ( p < 0.001)], respectively.…”
Section: Unclear Criteria Of Outcome Indicatorsmentioning
confidence: 99%